What drives major tax reform? Implications for taxing the rich - Beretta, M; Guceri, I; Jakobsen, K (Oxford University Press, 2023)
This paper examines some drivers behind substantial changes in tax policy in recent decades. Using existing theories and our definition of ‘beneficial major tax reforms’, we discuss three case studies: the US in the 1980s, the UK in the 1980s, and the UK’s failed ‘mini-budget’ of 2022. Our analysis reveals that the US’s TRA86 has, to some degree, improved efficiency, while the UK reforms may have exacerbated inequality with ambiguous effects on efficiency. Finally, we outline the potential for future reforms and conclude that political conditions are more likely to instigate major change than economic motivations.